2012
DOI: 10.1515/hf.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of resol-type phenol-formaldehyde resins prepared from H2SO4- and HCl-catalyzed phenol-liquefied Cryptomeria japonica wood

Abstract: Wood of Cryptomeria japonica (Japanese cedar) was liquefied in phenol with H2SO4 or HCl as catalysts and used as raw materials to prepare phenol-formaldehyde (PF) resins. The curing behavior and adhesion properties of resins prepared were investigated. Wood liquefied with H2SO4 as a catalyst had better liquefaction effect than that with HCl; however, the reaction of resin synthesis was hard to control due to its quickly increasing viscosity. Differential scanning calorimetry analysis shows that PF resins prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…1 The common catalysts of phenol-formaldehyde resole synthesis are sodium, potassium, lithium hydroxides and rarely hydroxides of divalent metals such as magnesium, calcium, or barium. [1][2][3] At the start of the resol synthesis, highly exothermic methylolation reactions between phenol and formaldehyde yield methylol phenols. The methylolation stage of the synthesis is followed by the condensation stage, in which the methylol groups react with the free sites of other phenolic species yielding methylene bridge structures between the phenolic rings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The common catalysts of phenol-formaldehyde resole synthesis are sodium, potassium, lithium hydroxides and rarely hydroxides of divalent metals such as magnesium, calcium, or barium. [1][2][3] At the start of the resol synthesis, highly exothermic methylolation reactions between phenol and formaldehyde yield methylol phenols. The methylolation stage of the synthesis is followed by the condensation stage, in which the methylol groups react with the free sites of other phenolic species yielding methylene bridge structures between the phenolic rings.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The formation of dibenzyl ether bridges resulting from the reactions of two methylol groups is not favored under highly alkaline conditions. [1][2][3] The resole resin synthesis is halted when the appropriate degree of condensation in the resin (viscosity) has been achieved. These resole resins are generally provided under conventional heating in batch reactors for a couple of hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Žilnik and Jazbinšek (2012) described a recovery process for the phenolic fraction from various Py-oils. There are ambitious efforts to substitute phenol (Ph) in phenol-formaldehyde (PF) resins by phenolics from renewable resources (Geng et al 2007;Derkyi et al 2011;Lee et al 2011, Lee et al 2012cSahaf et al 2012;Lu and Wu 2013), and experiments with phenolic Py-oils could be promising in this context. Amen-Chen et al (2002a,b) prepared resol-type PF resins, in which 50% of the Ph was replaced with Py-oil, and the product was suited as a binder in manufacturing OSB.…”
Section: Introductionmentioning
confidence: 99%
“…PF resins prepared with a formaldehyde/phenol molar ratio of about 2.0 or above have a significant bonding strength even after boiling in water. Lee et al (2012b) liquefied Japanese cedar wood in phenol with H 2 SO 4 or HCl as catalysts, while the latter proved to be better in terms of reactivity of the resin and wet bonding strength of the product. Hassan et al (2009) showed that LW-based resins have low viscosity and sufficient stability for storage and thus are suited for manufacturing particleboards.…”
Section: Introductionmentioning
confidence: 99%